Management of undernutrition during preconception and pregnancy in an urban setting in North India - Dhabhai, Neeta; Chowdhury, Ranadip; Taneja, Sunita; Shekhar, Medha; Kaur, Jasmine; Mittal, Pratima; Dewan, Rupali; Bhandari, Nita (Frontiers in Public Health, 2024)
Introduction The prevalence of underweight in women of reproductive age (WRA) in South Asia remains unacceptably high. Underweight women suffer from lowered immunity, infertility, and a risk of developing non-communicable diseases. In pregnancy, undernutrition results in poor neonatal and maternal outcomes. We present the findings and the management strategy of undernutrition in the intervention group of preconception and pregnancy phase in the WING study in low to lower middle-income neighborhoods of North India. Methods We analyzed data from the intervention group of the Women and Infants Integrated Interventions for Growth Study (WINGS), an individually randomized factorial design trial where 13,500 women were enrolled from low to middle income neighborhoods of Delhi, 6722 women in the preconception and 2640 from the pregnancy group. Food supplements in the form of locally prepared snacks were given to provide necessary calories and protein requirements as per the Body mass index (BMI) during the preconception period and each trimester of pregnancy. The snacks (sweet or savory) and milk or egg as a source of high-quality protein were delivered at home and intakes were observed. Individual tracking and close monthly monitoring were done for compliance, besides screening and treatment of infections. Results The mean (SD) age of the enrolled women was 24.2 (3.1) years, approximately 35% of women had a height of <150 cm and 50% had schooling >12 years. 17% of women in preconception and 14 % in pregnancy intervention groups were Underweight. Approximately two-thirds of underweight women improved 9-12 months after management in the preconception group and the same proportion improved four weeks after management during pregnancy. The proportion of women with inadequate weight gain (IWG) during pregnancy, was more in women who were underweight during preconception. Discussion A comprehensive approach to managing undernutrition with high-quality energy-dense food supplementation substantially improved weight gain in women during preconception and pregnancy. Trial registration: Clinical Trial Registry India #CTRI/2017/06/008908 55 (http://ctri.nic.in/Clinicaltrials/pmaindet2.php?trialid=19339%26EncHid=%26userName=societyforappliedstudies)